TINGKAT PENGETAHUAN DAN PERILAKU MAHASISWI MENGENAI LEGALITAS DAN KEAMANAN KOSMETIK - Hani Sri Fitriani; Rizki Siti Nurfitria (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
Cosmetic is secondary needs for human life and commodities used by all ages the rise of illegal cosmetics findings in community, increased promoting by public figures while safe cosmetics knowladge of community has not been balanced. The purpose of this study was to determine the level of knowledge and behavior regarding cosmetic legality and safety in students of health faculty including pharmacy and non-pharmacy in Bhakti Kencana University. The research methodology used was descriptive observational with cross-sectional approach. Data was presented in quantitative and qualitative descriptive. Data retrieval was done through filling out questionnaires that had been tested for validity and reliability. Data were analyzed by Rank Spearman test and Mann-Witney test. The results showed that the level of knowledge and behavior of pharmacy and non pharmacy was in the fair category (65,85%) (56,09%) and (67,47%) (73,98%). There was a weak and significant positive relationship between level of knowledge and behavior of cosmetic use in non-pharmacy student with correlation coefficient 0.133 so as pharmacy student not significant with correlation coefficient of 0.02. There was significant relationship between faculty with the level of knowledge and behavior cosmetic use of pharmacy faculty and non-pharmacy faculty with a correlation coefficient 0.000 and 0.003.